Correction: Hirasawa et al. Comparative Analysis of Muscle Activity and Circulatory Dynamics: A Crossover Study Using Leg Exercise Apparatus and Ergometer. Medicina 2024, 60, 1260 - Nobuhiro Hirasawa; Yukiyo Shimizu; Ayumu Haginoya; Yuichiro Soma; Gaku Watanabe; Kei Takehara; Kayo Tokeji; Yuki Mataki; Ryota Ishii; Yasushi Hada (Medicina)
In the original publication [...]